1992
DOI: 10.1128/aac.36.6.1241
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of azithromycin compared with that of erythromycin against Actinobacillus actinomycetemcomitans

Abstract: The in vitro susceptibility of ActinobaciUlus actinomycetemcomitans to azithromycin, a new macrolide antibiotic of a new class known as azalides, was compared with that of erythromycin by the agar dilution method on Mueller-Hinton Haemophilus test medium. Eighty-two A. actinomycetemcomitans strains, 79 recent clinical isolates obtained from 40 periodontally healthy or diseased subjects, and 3 type strains were included in the study. Erythromycin showed poor in vitro activity against A. actinomycetemcomitans. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 31 publications
2
54
0
2
Order By: Relevance
“…Sefton et al 15 demonstrated that subjects receiving azithromycin together with scaling and root planing presented significantly greater reductions in counts of spirochetes and black-pigmented bacteria in subgingival plaque than controls at 5 months posttherapy. In vitro studies have also demonstrated that azithromycin has a good inhibition effect on A. actinomycetemcomitans 13 and P. gingivalis. 12 In comparing these findings one should be cautious, given that these studies have investigated the clinical and microbiological effects of adjunctive azithromycin in the treatment of patients with chronic periodontitis.…”
Section: Act Inomycesmentioning
confidence: 94%
See 1 more Smart Citation
“…Sefton et al 15 demonstrated that subjects receiving azithromycin together with scaling and root planing presented significantly greater reductions in counts of spirochetes and black-pigmented bacteria in subgingival plaque than controls at 5 months posttherapy. In vitro studies have also demonstrated that azithromycin has a good inhibition effect on A. actinomycetemcomitans 13 and P. gingivalis. 12 In comparing these findings one should be cautious, given that these studies have investigated the clinical and microbiological effects of adjunctive azithromycin in the treatment of patients with chronic periodontitis.…”
Section: Act Inomycesmentioning
confidence: 94%
“…10 Azithromycin is detected in high concentrations in periodontal tissues 11 and was found to be effective against periodontopathogenic bacteria in vitro. 12,13 It has been demonstrated that azithromycin improves periodontal health of chronic periodontitis (ChP) patients when used in combination with mechanical periodontal treatment. 14 Studies evaluating the effect of azithromycin on the periodontal microbiota of ChP showed inconsistent findings.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 It is active against A. actinomycetemcomitans, and its therapeutic levels in gingival crevicular fluid are sustained for at least 14 days after the last oral dose. 15,16 Previous studies have shown that accumulation of AZM inside human gingival epithelial cells facilitates killing of intraepithelial A. actinomycetemcomitans . 13 When active transport of AZM was inhibited by a competitive inhibitor, there was a significant decrease in the killing of intraepithelial bacteria.…”
mentioning
confidence: 99%
“…Microbiology research data states that mechanical treatment (scaling and root planing) alone was not able to completely eliminate bacterial pathogens, such as Actinobacillus actinomycetemcomitans from local and subgingiva, therefore antibiotic application was considered to be effective as an adjuvant. 6 Azithromycin is an effective antibiotic against gram-positive aerobic bacteria, gram negative, and strict anaerobes such as Bacteroides fragilis, Fusobacterium sp, Peptostreptococcus sp. In addition, azithromycin also showed good activity against Actinobacillus actinomycetemcomitans and Porphyromonas gingivalis.…”
Section: Preparation Of Cell Culturementioning
confidence: 99%
“…Its local usages are also expected to be more effective than erythromycin, and required a lower concentration than eritromisin. 6 In order to minimize the side effects of systemic-administered azithromycin and to make it more economical and affordable, the authors consider to prepare azythromycin as a local preparations. However its biocompatibility test needs to be carried out to determine the optimum concentration of therapeutical doses which will not harm the gingival and the surroundings tissues.…”
mentioning
confidence: 99%